Problems of unity of language and thinking in the process of terminological nomination - Aidarbek Қ.Ж.; Imanberdiyeva А.Б.; Abdullina Н.У. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The main aspect of semiotic research in linguistics is the question of the connection between the three components: the sign, the signified (the subject of meaning), and the signifier (how meaning is made). The authors of the article consider the processes of representation of sign in the form of linguistic means through an alternative form of nomination. They conclude that the alternative nominations study requires a thorough method analysis of nominations. Modern trends in terminology are aimed at a comprehensive description of the terminological nomination processes. It is characterized by the predominance of some types of nomination over others, and the connection of certain types of nomination with various linguistic reality spheres. Establishing such specificity for a specific terminology system is a result of a terminology process study, inherent in this area of the nomination. The relevance of this issue became the basis for this article, in which the terminological nomination is based on a practical analysis of the term formation process. Considering the relevance of both semiotics from a modern linguistics point of view, they show that the nomination process is an indicator of the thought and language unity.